Female Characters and Children's Characters in Brothers Grimm's Little Brother and Little Sister - Castro Cotta, Maria Amelia de [UNESP] (Univ Federal Espirito Santo, 2016)
This article aims to analyze the female characters and children's characters in the tale Little Brother and Little Sister, by Grimm brothers, exploring the possible relationships that count on the conditions of orphaned and abandoned children. The story allows us to take the word in its dialogic and polyphonic process. There alternating voices of the characters in the story, which are expressed by the relationship with each other, that because the statement is a reflection of social interrelation. The hypothesis underpinning the study is the assumption that the tales, as a literary work, transcending space and time of its production, and read today, mobilize images and raise debates about the possible interrelationships and on the positions and busy social places the child and the woman in today's society. The ideas of Vygotsky and Bakhtin, specifically the concepts of dialogism and drama, gave theoretical support to the analysis.
Keywords: Grimm Tales; Female Characters; Children's Characters